Improving Infinity Haircut Financial Performance using Financial Statements Projection - Harisman, Taufik; Darmansyah, Asep (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Financial performance of a company indicates the health condition of its organization, it is possible to be able to know current financial performance of a company by analyzing using various kinds of calculation. The main objective in this research is to project financial statement of a company based on its financial performance which would be assessed using financial ratio and common-sized analysis. By using time-series analysis to compare historical data of Infinity Haircut financial statement, it enables researcher to fine the root problem and propose improvements for Infinity Haircut. From the analysis, it was discovered that the profitability ratios in Infinity Haircut indicates a low financial performance. The cause of this problem is low value of profitability ratios that were caused by the low amount of total sales. The result of this analysis creates a projection which can be used as a target for Infinity Haircut in the future to have better financial performance.Keywords: Financial Performance, Financial Ratio, Financial Statement Projection.